Effect of Cryogenic Treatment Time on the Corrosion Resistance of Magnesium Alloy MIG Welded Joint - YANG Dong, WU Zhi - sheng, GONG Xiao - yuan, ZHANG Li (Cailiao Baohu, 2021)
In view of the poor corrosion resistance of magnesium alloy welded joints, liquid nitrogen was used as a refrigerant to conduct cryogenic treatment of AZ31 magnesium alloy MIG welded joints at -190 ℃ for different times, and then the full immersion corrosion test in 3.5% NaCl corrosion solution was carried out. Through weight - loss method, microscopic metallographic observation and XRD diffraction analysis, the effect of cryogenic treatment time on corrosion of magnesium alloy welded joints was discussed. Results showed that the corrosion resistance of magnesium alloy welded joint could be improved by controlling the time of cryogenic treatment reasonably. The corrosion resistance of welded joint after cryogenic treatment at -190 ℃ for 6 hour was better.